Advances in additive manufacturing processes and their use for the fabrication of lower limb prosthetic devices. (2nd January 2023) - Bhatt, Shaurya; Joshi, Deepak; Rakesh, Pawan Kumar; Godiyal, Anoop Kant
ABSTRACT: Introduction: Traditional methods of prosthesis fabrication are not efficient and user centric and are made for common purposes without focusing on individual demands of user which leads to rejection of prosthesis for long-term use. Utilizing advanced additive manufacturing techniques for fabrication of prosthesis makes the development process user centric and covers all the user demands thus providing better fit, comfort, and more stable gait rehabilitation for the user. Areas covered: The articles reporting fabrication of lower limb prosthesis and its socket are included in the study. Standard fabrication and additive manufacturing method are both systematically assessed by the reviewers. The review also covers the advanced methods of additive manufacturing that are presently being used for fabrication of rehabilitation devices. Expert opinion: Additive manufacturing method of fabrication of prosthesis provides more flexibility for manufacturing prosthesis parts as per demand of the user. The fabrication method takes into account the residual limb and thus makes the prosthesis user-specific providing better comfort and fit.